“DIGITAL DENTISTRY: PRINCIPLES, TECHNOLOGIES, AND CLINICAL APPLICATIONS” - Turumova Marjona Bakhodir kizi,; Ziyodov Muhammadkodir, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Digital dentistry is a new direction in the diagnosis and treatment of dental problems. Performing procedures using computer systems and 3D technologies helps to obtain fast, high—quality results. In addition, it facilitates the study of research results and treatment planning.